The Impact of Women Board Members on ROA and Sustainability in CEO-Only Boards - Stone, Debra L.; Koleyni, Kayhan (Journal of Accounting and Finance, 2022)
Gender diversity has changed the board of directors and now with more women on the board (WOB), they can make significant changes in corporations and possibly outcomes. This study addresses the relationship between ratio of women on CEO-only boards with Corporate Social Responsibility (CSR), words disclosed in 10-K financial reports and Return on Assets (ROA). We found a significant negative relationship between ratio of WOB and CSR type words in the 10-k annual report and a significant positive relationship between ratio of WOB and ROA. Our results indicate no significant relationship between high or low WOB and sustainability type reports.